Arctic Environmental Test of Aircraft Armament. - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1969)
The Environmental Test Procedure describes test methods and techniques for evaluating the performance and characteristics of aircraft armament, under Arctic winter conditions, relative to the criteria contained in Qualitative Materiel Requirements, Small Development Requirements, Technical Characteristics or other applicable requirements or specifications. (Author)